Simplicity, Accountability and Relationships: Three ways to ensure MEL supports Adaptive Management - Roche, Chris (2018)
Based on a recent discussion in Manila, Chris Roche reflects on how Mo nitoring, Evaluation and Learning can better support 'adaptive program ming'.